Nonsyndromic Cleft Lip with or without Cleft Palate in Arab Populations: Genetic Analysis of 15 Risk Loci in a Novel Case-Control Sample Recruited in Yemen - Aldhorae, Khalid Ahmed; Bohmer, Anne C.; Ludwig, Kerstin U.; Esmail, Ahlam Hibatulla Ali; Al-Hebshi, Nezar Noor; Lippke, Bärbel; Golz, Lina; Nothen, Markus M.; Daratsianos, Nikolaos; Knapp, Michael (Wiley, 2014)
Background: Nonsyndromic orofacial clefting (nsOFC) is among the most common of all congenital disorders and has a genetically complex etiology. Based on embryological and epidemiological data, the phenotype can be differentiated into nonsyndromic cleft lip with or without cleft palate (nsCL/P) and nonsyndromic cleft palate only, with nsCL/P being the most frequent form. Recent genetic research, predominantly performed in populations from Europe and Asia, has identified numerous genetic susceptibility loci for nsCL/P. As only few data are available concerning genetic susceptibility to nsCL/P in Arab populations, we investigated a newly recruited nsOFC sample from Yemen. Methods: For each of the 15 currently known nsCL/P risk loci, the top single-nucleotide polymorphism (plus nine back-up variants) were genotyped in 242 nsCL/P cases and 420 healthy controls. Results: Single-marker association analysis revealed significant associations for four loci (8q24, 9q22, 10q25, 13q31). The strongest association was for the European high risk locus at 8q24 (Pcorrected = 5.09 10(-4) ; heterozygous odds ratio = 1.74 (1.22-2.47), homozygous odds ratio = 2.47 (1.55-3.93). Five additional loci (1q32.2, 3q12, 8q21, 17q22, 20q12) showed nominal significance that did not withstand correction for multiple testing. Although the six remaining loci (1p22, 1p36, 2p21, 3p11, 15q22, 17p13) failed to reach nominal significance, the risk alleles were in the same direction as in the discovery studies. Conclusion: The results suggest that four of the 15 analyzed nsCL/P risk loci which were identified in European and Asian ethnicities significantly confer risk for nsCL/P in Arab populations.